Manajemen Risiko dalam Konsep dan Implementasi GCG Terhadap Kinerja Operasional Perusahaan : Studi kasus pada Bank Swasta Nasional kantor cabang X - Agnes Imanuella Hutabarat (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Companies interact with various stakeholders in conducting their business activities, including directors/management, controlling and non-controlling shareholders, the government, employees, and the community. Resources are not limited to financial capital derived from shareholders or creditors, but also include intellectual capital and labor skills, regulatory capital, public services and infrastructure provided by the government, natural resource capital, and social capital from society. Corporate governance is a system of relationships among parties with an interest in a company or organization.In the implementation of Good Corporate Governance (GCG) in the banking sector, it is essential for banks to carry out a careful and phased approach based on an analysis of the bank’s conditions and level of readiness, so that GCG implementation can run smoothly and gain support from all elements within the bank. The Indonesian banking GCG guidelines explain that the regulation and implementation of GCG require strong commitment from top management and all organizational levels. Implementation begins with the establishment of basic policies (strategic policies) and a code of ethics that must be adhered to by all parties within the company.In the banking industry, risk refers to events with predictable and unpredictable potential that may negatively impact a bank’s income and capital. Therefore, at the initial stage of risk management implementation, banks must be able to identify risks comprehensively, both existing risks and those that may arise in the future. After a thorough identification process, banks conduct risk measurement, monitoring, and control. Risk measurement aims to enable banks to calculate the value of the risks faced so as to estimate their impact on capital. Operational risk is the risk arising from inadequate and/or failed internal processes, human error, system failures, and/or external events that affect company operations. Operational risk may originate from human resources, internal processes, systems and infrastructure, as well as external events.